Kontribusi Sektor Industri Informal TerhadapPembentukan Pendapatan Asli Daerah (Pad) KabupatenMadiun Dan Faktor-Faktor Yang Mempengaruhinya - Oktafiani, Renggar; , Muhammad Arif,SE.,M.Ec.Dev (2017)
This study attempts to analyze the number of business unit, employment, investment and production values the informal industrial sector of Locally generated revenue in Kabupaten Madiun for years 2011-2015. The research results show that fixed effect model (FEM) is the best panel data regression model. Based on the unison, get the result that in extent og signification 0,05 number of business unit, employment and investment informal industrial sector have a impact on Locally generated revenue in Madiun for years 2011-2015. Based on validity of influence, the number of business unit it has some positive effect significantly to Locally generated revenue, employment it has some negative effect significantly to Locally generated revenue and investment it has some positive effect significantly to Locally generated revenue.